Differentiation of technical and tactical training of epee fencers with the account of weapon control - Briskin, Y.; Pityn, M.; Perederiy, A.; Zadorozhna, O.; Smyrnovskyy, S.; Semeryak, Z. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2020)
Background. The evolution of competitive activities in fencing have given rise to the development of a system of training for competitive activities. Since it has proved impossible to increase the volume and intensity of the practice load for fencers, the problem of finding new ways and provisions to improve various aspects of fencers` proficiency has cropped up. In the development of fencing several different ways of weapon control have been developed in epee fencing, which involve the application of the French or pistol grip. At present the number of epee fencers in the top 16 world ranking who have applied the French hilt during the last 6 years make up 34 % of both males and females. Problem and aim. Until recently the sports scientists in this country have failed to broach the subject of weapon control in epee fencing at the appropriate level, while fencer training systems take no account of the specificity of weapon control. The aim of the study is the improvement of the technical and tactical training of epee fencers by means of differentiation of weapon control. Methods. The following methods were used: theoretical analysis and generalization, the documentary method, pedagogical observation, survey, experiment and methods of mathematical statistics. Results and Conclusions. The differences between the technical and tactical actions of high level fencers were defined. A program to differentiate the technical and tactical training of epee fencers was created. The effectiveness of the program was confirmed by pedagogical experiment.